Designing a specific agility test for free style wrestling - Rezaei, R.; Rajabi, H.; Reza Dehkhoda, M.; Habibi, H. (International Journal of Wrestling Science, 2013)
The purpose of this study was to develop a reliable, valid and specific agility test for freestyle wrestling. 62 wrestlers participated in this research. 23 wrestlers from wrestling clubs in Tehran were used for a pilot study in designing the agility test. 29 wrestlers from a Tehran team were selected as Tehran group (TG). In this group 10 of them had won medals in the Asian championships, world championships, or had been invited to be on the Iran freestyle wrestling national team and were considered as the elite group (EG). Additionally, there were also 10 non- elite wrestlers forming the non-elite group (NG). These groups were used to study the validity and reliability of the specific agility test. Wrestlers were tested three times on a specific reactive agility test (RAT) and twice on pre-planned agility test )PPAT( and once on 4×9 meter shuttle run test. Data analyzed from the TG was used for reliability analysis. For obtaining validity, EG results were compared with NG. Statistical analyses revealed significant correlation between the 4×9 shuttle run and the PPAT, 0.75 and 0.70 respectively, between 2 times of PPAT )0.87( and between 2 series of RAT (intraclass correlation coefficient = 0.87). Statistical analyses also showed significant difference between the EG and the NG (p < 0.05) in RAT time means. According to the results, RAT was reliable and valid for freestyle wrestling, and as it called here, the TMUWAT (Tarbiat Moalem University Wrestling Agility Test) and would be suggested for free style wrestlers. Performance differences on the RAT were attributed to the differences in perceptual skills and/or reaction ability. Testing and training agility should therefore stress those dimensions of agility and not only PPAT.